City of Liverpool : Maternity and Child Welfare
1928-01 1928 1920s 5 pages Maternity and Child Welfare. Work at Infant Welfare Centres during JANUARY 1928, as per Returns received. 2P.2883.250.10/27.Est No. of Sessions held during the month Infants' Consultations Mothers' Consultations Classes at Centres Nourishment provided Home Visits paid to Children References to Public Health Department, Hospitals, &c. Cash received Salaried Workers Voluntary Workers New Cases Total Visits New Cases Total Visits Total Attendances Mothers Infants New Cases Total Visits New Cases Total Visits £ s. d. Carnegie Centre 16 103 1206 90 1169 51 163 842 100 71 12 2 70, Everton Road 17 136 1571 132 1474 41 319 1387 116 4 10 15-17, Upper Parliament Street 17 59 1416 50 1339 328 619 65 37 1 4 Bankhall Institute 8 35 521 30 501 134 486 39 38 19 0½ St. Martin's Hall, Scotland Road 9 71 652 63 643 111 131 83 14 15 2½ Parish Hall, Walton 8 63 762 55 720 108 591 8 71 9 2½ 201, Rathbone Road 9 37 513 36 494 96 460 25 32 6 6 1/3 196, Beaufort Street 8 36 389 35 375 38 86 21 4 7 1 1/3 Garston Clinic 4 25 215 25 215 40 29 206 10 24 5 3½ 56. Vauxhall Road 4 34 214 27 197 74 140 28 8 2 4½ West Derby Clinic 4 33 364 33 364 59 298 Child Welfare Association No returns. Maternity Hospital Welcome 5 58 562 42 120 115 6 4 88 105 Liverpool Babies' Hospital Woolton 5 18 380 2 9 4 Classes 9 14 1½ Village Hall Knotty Ash 4 17 25 17 25 2 16 5½ Dental Clinic. 18 0 118 725 6800 635 7656 247 1467 5229 88 613 2430 11 8½ 292/824/1/124-125